1970
DOI: 10.1152/ajplegacy.1970.218.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Influences of duodenal acidification on acid and pepsin secretion of the stomach in dogs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…This observation was consistent with the antagonism of gastrin I for secretin and cholecystokinin on the pyloric muscle since duodenal acidification releases both hormones (4,5). The relevance of these observations to the function of the pylorus must be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This observation was consistent with the antagonism of gastrin I for secretin and cholecystokinin on the pyloric muscle since duodenal acidification releases both hormones (4,5). The relevance of these observations to the function of the pylorus must be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanism by which the human pylorus contracts in response to the intraduodenal instillation of amino acids, olive oil, and HC1 is not known. It has been presumed to be hormonal because the substances which were instilled into the duodenum are known to release both secretin and cholecystokinin (4)(5)(6)(7)(8)(9)(10)(11). In addition, a precedent for hormonal regulation of other gastrointestinal sphincters has been established (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…When the pH fell below 215 the secretion of acid and pepsin in response to food and insulin was inhibited. Nakajima & Magee (1970) confirmed these results in Heidenhain pouch dogs. The observation that acid in the duodenum releases secretin when the pH is less than 5 (Meyer & Grossman, 1971) suggested that the intestinal hormone responsible for the physiological control of peptic secretion might indeed be secretin.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, it has been shown that the gastrointestinal hormone, gastrin, has a physiological role in the control of sphincter strength (5,6). Since a well-known relationship exists between gastrin and secretin in the hormonal control of gastric acid secretion (7)(8)(9)(10)(11)(12) and gastric motor function (13)(14), it seemed possible that these hormones also interact to regulate lower esophageal sphincter competence. This study is designed to quantitatively assess the interaction of endogenous and exogenous gastrin and secretin in the regulation of lower esophageal sphincter competence in man.…”
Section: Introductionmentioning
confidence: 99%